2018
DOI: 10.1039/c8cc05505j
|View full text |Cite
|
Sign up to set email alerts
|

Z-Schematic and visible-light-driven CO2 reduction using H2O as an electron donor by a particulate mixture of a Ru-complex/(CuGa)1−xZn2xS2 hybrid catalyst, BiVO4 and an electron mediator

Abstract: Visible-light-driven Z-schematic CO2 reduction using H2O as an electron donor was achieved using a simple mixture of a metal-sulfide/molecular hybrid photocatalyst for CO2 reduction, a water oxidation photocatalyst and a redox-shuttle electron mediator. This is the first demonstration of a highly selective particulate CO2 reduction system accompanying O2 generation utilizing a semiconductor/molecular hybrid photocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 39 publications
0
54
0
4
Order By: Relevance
“…For example, Sato et al reported a hybrid system composed of a Ru molecular catalyst modified p‐InP photocathode and a TiO 2 or SrTiO 3 photoanode for simultaneous CO 2 reduction and water oxidation, respectively, under ultraviolet light irradiation . Kudo and co‐workers constructed a hybrid Z‐schematic system using [Ru(dpbpy)] (dpbpy = 4,4′‐diphosphonate‐2,2′‐bipyridine) modified (CuGa) 1− x Zn 2 x S 2 as photocatalyst for CO 2 reduction and BiVO 4 as an efficient visible‐responsive photocatalyst for water oxidation along with a [Co(tpy) 2 ] 3+/2+ redox mediator, achieving efficient CO 2 reduction in an aqueous solution and stoichiometric oxygen evolution simultaneously . Further improvement of Z‐scheme artificial photosynthesis system has been hindered by backward reactions involving reversible redox mediators.…”
Section: Water Oxidation In Artificial “Z‐scheme” Photosynthesis Systemsmentioning
confidence: 99%
“…For example, Sato et al reported a hybrid system composed of a Ru molecular catalyst modified p‐InP photocathode and a TiO 2 or SrTiO 3 photoanode for simultaneous CO 2 reduction and water oxidation, respectively, under ultraviolet light irradiation . Kudo and co‐workers constructed a hybrid Z‐schematic system using [Ru(dpbpy)] (dpbpy = 4,4′‐diphosphonate‐2,2′‐bipyridine) modified (CuGa) 1− x Zn 2 x S 2 as photocatalyst for CO 2 reduction and BiVO 4 as an efficient visible‐responsive photocatalyst for water oxidation along with a [Co(tpy) 2 ] 3+/2+ redox mediator, achieving efficient CO 2 reduction in an aqueous solution and stoichiometric oxygen evolution simultaneously . Further improvement of Z‐scheme artificial photosynthesis system has been hindered by backward reactions involving reversible redox mediators.…”
Section: Water Oxidation In Artificial “Z‐scheme” Photosynthesis Systemsmentioning
confidence: 99%
“…In this system, the Ru(II) complex was again used as the catalyst for CO 2 reduction. 3 The reported systems exhibit a low selectivity of CO 2 reduction against H 2 evolution and insufficient durability. It is again emphasized that, in these systems, light absorbers are the semiconductor materials, and the Ru(II) complex works only as the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…(c) Schematic illustration of the formation of hybrid CuO-TiO 2 À x N x hollow nanocube and its FESEM images [76]. (d) Z-schematic system of visible light-driven CO 2 reduction of [Ru(dpbpy)]-modified (CuGa) 1 À x Zn 2x S 2 hybrid photocatalyst, BiVO 4 photocatalyst, and [Co (tpy) 2 ] 3+/2+ redox shuttle electron mediator [78]. (Reproduced permission from The Royal Society of Chemistry.)…”
Section: Hybrid Nanostructure Constructionmentioning
confidence: 99%